Liars : a novel - Manguso, Sarah, 1974- (Hogarth, 2024)
"A nuclear family can destroy a woman artist. I'd always known that. But I'd never suspected how easily I'd fall into one anyway. When Jane, an aspiring writer, meets filmmaker John Bridges, they both want the same things: to be in love, to live a successful creative life, and to be happy. When they marry, Jane believes she has found everything she was looking for, including--a few years later--all the attendant joy and labor of motherhood. But it's not long until Jane finds herself subsumed by John's ambitions, whims, and ego; in short, she becomes a wife. As Jane's career flourishes, their marriage starts to falter. Throughout five house moves, two failed businesses, and a steady draining of the family finances, Jane tries to hold it all together. That is until John leaves her."--